O "monstro de Erechim" : um estudo de caso sobre o imaginário do medo (1980) - Rocha, Humberto José da (2008)
This dissertation deals a series of crimes occured in the city of Erechim-RS in the 1980 decade by a man named Luiz Baú, that the profile of these crimes, would be known throughout the state as the "monster of Erechim". Besides the historical narrative around crime, where consider the historical context of the time, this work also seeks to analyze the repercussion of these crimes on aspects sociological, psychological and legal. Initially, running over mainly the psychology, geral frame that would have conditioned the protagonist to become a criminal, besides shows to the first crime of a series. Arrested for this crime, analyzes the period from prison in State Prison of Erechim, for such uses run overs mainly to the law. With the flight of the protagonist of prison, back the period that was released by the city of Erechim, when would commit four murders, having a significant influence in popular imagination of the city. Again arrested, to probe the verge of linchamento by the population of Erechim, and the consequense removal of the accused to the Psychiatric Institute Forense, in Porto Alegre. From the internment at the Institute seeks discuss how the case was treated by justice and the memory of the population of Erechim. Finally, points for the outcome of the case.